Identification of Fault Zone in Bali Using GGMPlus Gravity and Alos-2 Palsar-2 Data - I Putu Dedy Pratama; Takahiro Osawa; Abd Rahman As-Syakur (Universitas Negeri Medan, 2023)
The local active fault in Bali has a small magnitude (M<5) but has destructive potential because it is very close to residential areas. Mapping the fault area on Bali is needed to identify the parameters of faults. This study used gravity data from GGMplus, topographic data from DEMNAS, and lineaments using ALOS-2 PALSAR-2 data. Validation and interpretation using the geological map of Bali and seismicity data. We interpret the subsurface using the gravity derivative method to identify the type of fault movement. Identify fault locations using lineament extraction from SAR data processed by directional filters. The composite image red-green-blue (RGB) for HH, HV, and VV polarization was used for automatic lineament extraction and then corrected manually. The results of the gravity method succeeded in identifying 29 of the 30 faults from the geological map of the Bali sheet and a new spot from PALSAR-2. Bali land has 12 thrust faults, 11 strike-slip faults and six normal faults. The image of PALSAR-2 (L band) has succeeded in making a fault lineament map for the Bali region. The lineament extraction results from PALSAR-2 obtained four new faults (Pesanggaran, Sepang, Tegal Badeng, and Banyuwedang), while four faults were not identified (Tampaksiring Fault, Plaga, Mambal, and Munduk-Rajasa). NE-SW dominates the strike directions, and the dip angles are 45-80 degrees. We propose 30 faults in Bali, including 26 defects from geological maps with changes in length and location shift and four new marks extracted from automatic lineament.Keywords: Remote Sensing, Earthquake, Derivative Gravity, Lineament, SAR